2015
DOI: 10.1007/s40071-015-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics in the trophic status of water, floral and faunal density along some selected coastal areas of the Red Sea, Tabuk, Saudi Arabia

Abstract: Eutrophication is posing a threat to the coastal marine ecosystems. The consequence of anthropogenic induced eutrophication of waters has resulted in severe deterioration of surface waters. In this research a preliminary data was collected on eutrophication by environmental monitoring on some selected coastal areas of the Red Sea near Tabuk, Saudi Arabia. Sampling sites were selected from Haql, Sharmaa and Duba (five for each station) and water samples collected in four different seasons (Oct 2013, Jan 2014, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Environmental factors including temperature, pH, light intensity, nutrient availability, and precipitation influence plant physiology and biochemistry [62]. The seasonal dynamics of the floral and faunal density and the tropic status of water was assessed by Ansari et al (2015), expressing its research importance [63]. The algal biodiversity and the growth is altered due to climatic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors including temperature, pH, light intensity, nutrient availability, and precipitation influence plant physiology and biochemistry [62]. The seasonal dynamics of the floral and faunal density and the tropic status of water was assessed by Ansari et al (2015), expressing its research importance [63]. The algal biodiversity and the growth is altered due to climatic changes.…”
Section: Discussionmentioning
confidence: 99%
“…The coastline of Tabuk region along the Red Sea is the harbor for marine algae. As per the literature survey and the published reports in Tabuk region, seasonal dynamics and ecological parameters of marine algae are recorded by various workers [5,[32][33][34][35][36]. However, Al Solami (2020) [37] studied the comparative response of red and green algae in relation to the quality of coastal waters of Red Sea at Haql region.…”
Section: Algal Biodiversitymentioning
confidence: 99%
“…Ibraheem et al (2014) [40] reported some algal species from Umluj coasts of the Red Sea, namely, Enteromorpha intestinalis, Padina pavonia, Cystoseira myrica, Cystoseira trinodis, Colpomenia sinuosa, Turbinaria ornate, Sargassum latifolium, Laurencia majuscule, Laurencia catarinensis, Laurencia papillosa, Laurencia sp., Laurencia sp., Liagora hawaiiana Butters, Hypnea bryoides Børgesen, Palmaria palmate, Galaxaura rugose, Gracilaria arcuate, Acanthophora spicifera, and Digenia simplex. Ansari et al (2015) [5] studied eutrophication in coastal waters, and floral and faunal density in relation to the seasonal dynamics of some selected coastal areas at Haql, Sharma and Duba of the Red Sea in Tabuk region. Only few coastal sites showed eutrophic characteristics.…”
Section: Algal Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Extreme diel fluctuations of oxygen concentration have also been observed in major Red Sea ecosystems, including coral reefs, mangroves, and seagrass meadows, ranging from 0.1 to 8.9 mg O 2 L -1 (Omar, 2013;Harabi and Affan, 2016;Roik et al, 2016;Giomi et al, 2019;Masoud et al, 2019) with extremely low DO levels occurring at nighttime. At the central Red Sea, a tidal node (tidal amphidrome) leading to minimal tidal ranges 0.2 m (Madah et al, 2015;Gharbi et al, 2018), localized nutrient enrichments (Dunne et al, 2021) and coastal eutrophicationinduced hypoxia (Duarte, 1995;Ansari et al, 2015) can all lead to increased fluctuations in oxygen availability by fueling respiratory oxygen demand. Therefore, complex ecological patterns can emerge as a result of short-term oxygen availability with increasing respiratory demands during nighttime, even over a few hours (Altieri et al, 2021;Dubuc et al, 2021;Johnson et al, 2021) or at very shallow water despite the influence of tidal change (Truchot and Duhamel-Jouve, 1980;DeCarlo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%